Does Timing Matter? Associations Between Intimate Partner Violence Across the Early Life Course and Internalizing and Externalizing Behavior in Children - Moss, Katrina M. (Journal of interpersonal violence, 2023)
The association between exposure to intimate partner violence (IPV) and child behavior problems is well established. However, questions remain about whether the timing during the child’s early life course matters. We used a structured life course approach to investigate associations between the timing of IPV and children’s internalizing and externalizing behaviors. Participants were from the Australian Longitudinal Study on Women’s Health (ALSWH), a national, randomly sampled community-based study that has surveyed women every 3 years since 1996. For this study, mothers born 1973 to 1978 (N = 2,163) provided data on their three youngest children under 13 years (N = 3,697, 48.5% female) as part of the Mothers and their Children’s Health (MatCH) study in 2016/2017. Mothers indicated IPV in ALSWH using the Community Composite Abuse Scale in early (M = 0.99 years, SD = 0.88 years) and middle childhood (M = 3.98 years, SD = 0.92 years), and before birth (preconception). Mothers rated child internalizing and externalizing behavior in MatCH (child age: M = 8.15 years, SD = 2.37 years) using the Strengths and Difficulties Questionnaire. We tested critical period, sensitive period, and accumulation hypotheses by comparing the fit of nested linear regression models (separately for girls and boys). Mothers were predominantly Caucasian (>90%) and university educated (65.5%), and 41.7% reported financial stress. Most children were not exposed to IPV (68.1%). Of those who were, 55.2% were exposed at one time, 28.7% at two times, and 16.1% at all three. Accumulation was the best model for externalizing in boys and girls and for internalizing in girls. A critical period in middle childhood was identified for internalizing in boys. Overall, the duration of exposure was more important than the timing. This suggests early detection is essential in mitigating the impact of IPV on children, with particular attention needed for boys exposed to IPV in middle childhood.